Revealing the intrinsic superconducting gap anisotropy in surface-neutralized BaFe2(As0.7P0.3)2 - Ziming Xin (Nature Portfolio, 2021)
The lack of a clean charge neutral cleavage plane for the 122 family of iron-based superconductors has complicated surface-sensitive spectroscopy probes from revealing the intrinsic electronic properties of these materials. Here the authors introduce an effective surface dosing method that drastically improves the observed spectral quality, thus revealing unprecedented details of the superconducting gap anisotropy.